Problems of State Authority in Regulating Religious Holiday Bonuses for App-Based Drivers: A Normative Legal Analysis - Azzahra, Salwa; Budiono, Rachmad; Santoso, Budi (International Journal of Business, Law, and Education, 2026)
The expansion of the digital economy has transformed the organization of work, particularly through platform-based transportation and delivery services. In Indonesia, app-based drivers and couriers are generally constructed not as employees, but as partners operating under civil-law agreements with platform companies. This legal construction places them outside the ordinary scope of labour-law protection, including the statutory regime governing Religious Holiday Allowances (Tunjangan Hari Raya Keagamaan/THR) for workers. Nevertheless, growing demands for welfare protection prompted the Minister of Manpower to issue Circular Letter Number M/3/HK.04.00/III/2025 concerning the provision of Religious Holiday Bonuses (Bonus Hari Raya Keagamaan/BHR) for app-based drivers and couriers. This article examines the legal problems arising from state authority in regulating BHR for platform workers. Using normative legal research with statutory and conceptual approaches, this study analyses labour legislation, administrative-law doctrines, partnership law, ministerial circular letters, and scholarship on platform work. The study finds that the Circular Letter reflects a welfare-oriented administrative response, but it also raises serious juridical concerns because it seeks to influence private partnership relations through an instrument that lacks binding normative force. The problem lies not in the protective objective, but in the mismatch between the regulatory aim and the legal instrument used. The article argues that Indonesia requires a specific and rule-based regulatory framework for platform-based labour relations, including minimum social protection, algorithmic accountability, and a sui generis legal status for platform workers.